STANDARDIZATION OF CARDIAC CATHETERIZATION IN CHILDREN WITH CONGENITAL HEART DISEASES WITH SYSTEMIC-TO-PULMONARY COMMUNICATIONS (International Seven Journal of Multidisciplinary, 2026)
Cardiac catheterization plays a fundamental role in the evaluation of congenital heart diseases with systemic-to-pulmonary communications, whose main complication is pulmonary arterial hypertension. The lack of consensus in the literature regarding the assessment of pulmonary vascular resistance in pediatrics poses challenges for defining operability and therapeutic management. This cross-sectional and prospective study, conducted at the Heart Institute (InCor HCFMUSP), aimed to describe accurate hemodynamic parameters in patients up to 3 years of age with biventricular physiology and nonrestrictive communications. Data collection was performed under ideal conditions, including baseline measurements and vasoreactivity testing with inhaled nitric oxide. The Fick method was used to calculate flows and vascular resistances through serial blood gas analyses at multiple sites (vena cavae, pulmonary arteries, aorta, and pulmonary vein). The results, consolidated in an automated spreadsheet, provide a reliable basis for the descriptive analysis of intra-procedural events and hemodynamic management strategies, contributing to the standardization of this procedure in the pediatric age group.